2018
DOI: 10.4103/jcrt.jcrt_849_17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between resilience, social support as well as anxiety/depression of lung cancer patients

Abstract: Lower psychological anxiety and depression would be experienced by lung cancer patients with higher resilience and social support. The level of anxiety and depression would be indirectly affected by social support through the mediation of resilience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 33 publications
6
24
0
Order By: Relevance
“…We found that depressed patients had significantly lower CD-RISC scores than non-depressed patients. This CD-RISC result is partially supported by the findings of a previous study, which suggested that the high levels of depression among LC patients were related to poor resilience 30. Resilience indicates the ability of patients to protect or recover their mental health despite the existence of objective difficulties, eg, cancer 29.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We found that depressed patients had significantly lower CD-RISC scores than non-depressed patients. This CD-RISC result is partially supported by the findings of a previous study, which suggested that the high levels of depression among LC patients were related to poor resilience 30. Resilience indicates the ability of patients to protect or recover their mental health despite the existence of objective difficulties, eg, cancer 29.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to the aforementioned associated factors of depression in LC patients, stress, anxiety symptom, and resilience are also common psychosocial problems among cancer patients 14,2630. Resilience is defined as abilities and traits of individuals, which help patients to quickly overcome adversity and stress, and regain the normal psycho-emotional state 29,30. Prior studies have demonstrated that resilience, positive adaptation to protect from psychological distress, is not only associated with quality of life but also a predictor of quality of life in cancer patients 31.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to symptoms of depressions, it is known that stressful life situations and events, risk behaviors, behavioral excesses and negative emotions experienced throughout life are significant for the onset of these symptoms during old age ( 45 ) .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Further studies suggest relations between high levels of resilience and lower levels of anxiety and depression. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 40 Further, disease-specific measures seem to be more sensitive for the detection of small changes in interventional or longitudinal studies. 29 However, clinicians report, that even (asymptomatic) precursors of MM (that are not treated yet) seem to be associated with a deterioration of HRQOL and augmented psychological burden. Therefore, we used a generic measure that offers the opportunity to compare outcomes across different populations including asymptomatic prestages of MM.…”
Section: Discussionmentioning
confidence: 99%